The dynamics of the national minimum wage: transitions between different labour market states - Melanie K. Jones; Richard J. Jones; Philip D. Murphy; Peter J. Sloane (Institute for the Study of Labor (IZA), 2005)
An important policy issue is whether the National Minimum Wage (NMW) introduced in Britain in April 1999, is a stepping stone to higher wages or traps workers in a low-wage no-wage cycle. In this paper we utilise the longitudinal element of the Labour Force Survey over the period 1999 to 2003 to model transitions between different labour market states payment at or below the NMW, above the NMW, unemployment and inactivity, using a multinomial logit approach. It appears that for many workers payment at or below the NMW is of relatively short duration and a substantial number move into higher paid jobs.
Keywords: J0; J3; J6; 330; national minimum wage; transitions; steady state distributions